2017
DOI: 10.1093/annonc/mdw685
|View full text |Cite
|
Sign up to set email alerts
|

Preference for subcutaneous or intravenous administration of rituximab among patients with untreated CD20+ diffuse large B-cell lymphoma or follicular lymphoma: results from a prospective, randomized, open-label, crossover study (PrefMab)

Abstract: NCT01724021 (ClinicalTrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 15 publications
7
93
1
4
Order By: Relevance
“…In addition, most of these ARRs resolved spontaneously, as drug delay was only reported in one patient and no treatment discontinuation was required. These safety results, including the 48Á6% of ARRs and the 7Á9% presentation of injection site erythema, are in line with the acceptable safety profile reported in clinical trials that assessed subcutaneous rituximab administration (Salar et al, 2014;Davies et al, 2014Davies et al, , 2017bRummel et al, 2017;Lugtenburg et al, 2017). The SABRINA (FL) and MabEase (DLBCL) trials showed the occurrence of ARRs in 20Á9-48Á2% of patients during up to 7 cycles of subcutaneous rituximab for the first-line induction treatment of FL and DLBCL, mainly manageable mild to moderate events À only reaching grade 3 in 2Á7-3Á1% of patientsÀ, which most frequently included injection-site reactions (≥5%), such as erythema, pruritus, rash, pain, bruising, discoloration, haematoma, hypertrophy, induration or inflammation/swelling (Lugtenburg et al, 2017;Davies et al, 2017b).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, most of these ARRs resolved spontaneously, as drug delay was only reported in one patient and no treatment discontinuation was required. These safety results, including the 48Á6% of ARRs and the 7Á9% presentation of injection site erythema, are in line with the acceptable safety profile reported in clinical trials that assessed subcutaneous rituximab administration (Salar et al, 2014;Davies et al, 2014Davies et al, , 2017bRummel et al, 2017;Lugtenburg et al, 2017). The SABRINA (FL) and MabEase (DLBCL) trials showed the occurrence of ARRs in 20Á9-48Á2% of patients during up to 7 cycles of subcutaneous rituximab for the first-line induction treatment of FL and DLBCL, mainly manageable mild to moderate events À only reaching grade 3 in 2Á7-3Á1% of patientsÀ, which most frequently included injection-site reactions (≥5%), such as erythema, pruritus, rash, pain, bruising, discoloration, haematoma, hypertrophy, induration or inflammation/swelling (Lugtenburg et al, 2017;Davies et al, 2017b).…”
Section: Discussionsupporting
confidence: 81%
“…The SABRINA (FL) and MabEase (DLBCL) trials showed the occurrence of ARRs in 20·9–48·2% of patients during up to 7 cycles of subcutaneous rituximab for the first‐line induction treatment of FL and DLBCL, mainly manageable mild to moderate events − only reaching grade 3 in 2·7–3·1% of patients−, which most frequently included injection‐site reactions (≥5%), such as erythema, pruritus, rash, pain, bruising, discoloration, haematoma, hypertrophy, induration or inflammation/swelling (Lugtenburg et al , ; Davies et al , ). Although the PrefMab (FL and DLBCL) trial reported lower rates of ARRs, ranging from 10·4% to 21·1% and with few overall cases of erythema (1·8%) or injection site erythema (1·5%), the differences in trial design should be noted, as this trial used a crossover approach of intravenous and subcutaneous rituximab administration with the latter being administered for up to 3–4 cycles (Rummel et al , ). With regard to maintenance treatment for FL, the SparkThera trial also supported an acceptable and manageable safety profile, with 31% of patients experiencing ARRs after subcutaneous rituximab injection for up to 2 years, which were mainly mild to moderate, rarely required treatment, and most commonly included erythema (13%), injection site erythema (5%) and myalgia (5%) (Salar et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent examples of the FDA using patient preferences to inform regulatory decisions are a recent FDA advisory committee approval of a subcutaneous formulation of rituximab in the treatment of blood cancers, supported in part by a patient preference study conducted within the trial [21,22], and the release of an FDA draft guidance [23] on developing treatments for Duchenne muscular dystrophy, in part informed by a proposed draft guidance developed by the patient group Parent Project Muscular Dystrophy, which conducted a patient preference study to support their draft [24].…”
Section: Patient Preferences In the Fda Regulatory Review Of Medical mentioning
confidence: 99%
“…Although some examples of the application of patient preference data to regulatory decisions exist [4,22,29], many questions remain about how to incorporate patient preference data in regulatory decisions and the standards that should be applied to these data. A number of organizations, including, but not limited to, patient groups, such as the National Health Council and FasterCures, industry associations, such as the Pharmaceutical Research and Manufacturers of America and the Biotechnology Innovation Organization, and public-private partnerships, such as the Medical Device Innovation Consortium in the USA and the Innovative Medicines Initiative in Europe, have suggested or are evaluating frameworks for systematically incorporating patient preference information in regulatory benefit-risk assessments.…”
Section: Moving Forwardmentioning
confidence: 99%